2005
DOI: 10.1111/j.1440-1711.2005.01303.x
|View full text |Cite
|
Sign up to set email alerts
|

Secretory products from infective forms of Nippostrongylus brasiliensis induce a rapid allergic airway inflammatory response

Abstract: Allergic asthma is responsible for widespread morbidity and mortality and its incidence has increased dramatically in industrialized countries over the past two decades. Here, we describe a new murine model of allergic asthma utilizing a novel allergen with intrinsic enzymatic activity similar to that reported for many environmental allergens. The allergen, NES, is excreted and secreted from the nematode Nippostrongylus brasiliensis, and can readily be isolated from in vitro parasite cultures. When NES is admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 32 publications
0
5
1
Order By: Relevance
“…Previous studies have shown that NES induces strong Th2-type immune responses in mice (18,25). These observations are in contrast to our findings in which NES clearly leads to the inhibition of Th2 responses.…”
Section: Nes Suppresses Ova-specific Th2 Responses and Simultaneouslycontrasting
confidence: 99%
“…Previous studies have shown that NES induces strong Th2-type immune responses in mice (18,25). These observations are in contrast to our findings in which NES clearly leads to the inhibition of Th2 responses.…”
Section: Nes Suppresses Ova-specific Th2 Responses and Simultaneouslycontrasting
confidence: 99%
“…Interestingly, such hemosiderin-laden macrophages are not present in the lungs of influenza-infected mice (data not shown), or during chronic allergen exposure despite strong inflammatory infiltrates. Moreover, prolonged administration of NES induces long-term AHR but does not lead to the development of emphysema, suggesting that late phase hemorrhage in lung tissue may flow on from the initial physical damage induced by worm migration through the lung tissue [12] (data not shown).…”
Section: Discussionmentioning
confidence: 94%
“…After migrating through the vascular wall, the worms reach the large airspaces where they are coughed up and swallowed within 3-4 days [11]. Nb is not retained in the lung, nevertheless, a Th2 immune response characteristic of allergic airway inflammation, is sustained within the lung for an additional 14 days after the larvae have migrated out, possibly due to remaining allergens [12]. This infectious disease model has been widely used to unravel the key immunological factors that underlie Th2 immune responses.…”
Section: Introductionmentioning
confidence: 99%
“…18 On the other hand, Nb-secreted proteins could induce selective maturation of DC, thus promote Th2 differentiation. 19,20 These results suggest that parasite-associate antigens are capable of bypassing the need of basophils (or of IL-4) to induce Th2 immunity. In a T. muris infection study, worm burden was significantly elevated following basophil depletion.…”
Section: Basophils Induce Th2 Immunitymentioning
confidence: 77%